Meningkatkan Public Speaking Dengan Baik Dan Benar Di Tpq Desa Mojodanu Kecamatan Ngusikan Jombang - nasirudin, mohamad; Ashar, Salim; Nashoih, Afif Kholisun; Ahmad, Arifuddin; Maulidiya, Fifin Izzatul; Aliyah, Himmatul; Khoir, Muhammad Abil; Hambali, Nur Habib Ahmad; Qomariyah, Umi Kulsum Nur (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
Knowledge related to public speaking will be able to facilitate opinions/ideas/information to be accepted by heterogeneous communities. Public speaking skills can also support students' careers in working to produce competent public speakers to meet the needs of today's era. Mojodanu is a village located in Ngusikan District, Jombang Regency. The ability to do Public Speaking among TPQ children in Mojodanu varies. Some of them are used to speaking in public through school activities and religious studies, but there are also those who still feel less confident. From here the author has an idea to improve the mastery of Public Speaking properly and correctly in Mojodanu Village, Ngusikan District. By using the Public Speaking Guide book. The approach method used in community service in Mojodanu Village is to use the PAR method (Participatory Action Research). One of them is by implementing practical methods, training and local community approaches so that indirectly children and the community in Mojodanu Village can capture the Public Speaking training material well. After the Public Speaking training was held, TPQ children in Mojodanu village were enthusiastic in preparing themselves for the Public Speaking competition. The opinion of the head of TPQ from various hamlets in Mojodanu Village said that TPQ children were happy and motivated in the Public Speaking training that we did. With the books provided, it can help partners in the teaching and learning process.